1994
DOI: 10.1037/0735-7044.108.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Declarative memory following anterior temporal lobectomy in humans.

Abstract: This study hypothesized that verbal memory decline following anterior temporal lobectomy (ATL) is associated with a lack of significant neuropathology in resected left, but not right, hippocampus and is limited to measures of episodic memory only. Tests of immediate (digit span), semantic (visual naming), and episodic memory as measured by the California Verbal Learning Test (CVLT) were administered before and 6 months after resection of the anterior left (n = 36) or right (n = 26) temporal lobe. There were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 26 publications
9
54
0
Order By: Relevance
“…Chelune et al (1991), Hermann, Wyler, Somes, Berry, and Dohan (1992), Hermann et al (1994), Ivnik et al (1987), Novelly et al (1984), Phillips and McGlone (1995), Rausch and Crandall (1982), Saykin, Gur, Sussman, O'Connor, and Gur (1989), Seidenberg et al (1996), Trenerry, Jack, Cascino, Sharbrough, and So (1996), Trenerry et al (1993), andSomes (1995) reported similar findings using LM-I raw scores or LM savings scores (LM delayed divided by LM immediate). Consistently, memory scores decline after LATL.…”
Section: Hypothesissupporting
confidence: 75%
See 1 more Smart Citation
“…Chelune et al (1991), Hermann, Wyler, Somes, Berry, and Dohan (1992), Hermann et al (1994), Ivnik et al (1987), Novelly et al (1984), Phillips and McGlone (1995), Rausch and Crandall (1982), Saykin, Gur, Sussman, O'Connor, and Gur (1989), Seidenberg et al (1996), Trenerry, Jack, Cascino, Sharbrough, and So (1996), Trenerry et al (1993), andSomes (1995) reported similar findings using LM-I raw scores or LM savings scores (LM delayed divided by LM immediate). Consistently, memory scores decline after LATL.…”
Section: Hypothesissupporting
confidence: 75%
“…Patients without hippocampal sclerosis reportedly are more at risk for surgical morbidity, as removal of a functional hippocampus is thought to be damaging to the ability to recall narrative prose, especially when the hippocampus contralateral to the surgery is impaired. Hermann et al (1992Hermann et al ( , 1994, Rausch and Babb (1993), Seidenberg et al (1996), and Trenerry et al (1993) reported this finding. We did not isolate this variable in our series, but attempted to test this hypothesis as suggested by Bell and Davies (1998) by including age at seizure onset as a surrogate variable.…”
Section: Age and Sexsupporting
confidence: 56%
“…Clearly, using the time of excision as this landmark is inadequate. Significant hippocampal damage is found in many patients with TLE before resective surgery (Miller et al, 1993), and the removal of a nonfunctional hippocampus may not produce any additional anterograde memory defect (Hermann et al, 1994). Our analysis of the episodic memory data according to age of onset of epilepsy speaks to this issue.…”
Section: Discussionmentioning
confidence: 86%
“…Pre-operative cognitive performance and the neuropathological status of the resected tissue have been shown to interact with post-surgical outcome (Stroup et al, 2003). In particular, individuals with normal appearing hippocampi and strong preoperative memory performances are at increased risk for memory impairment following surgery (Hermann et al, 1994;Loring, 1997;Powell, Polkey & McMillan, 1985;Trenerry et al, 1993). Interestingly, extent of tissue resection, per se, is not a consistent predictor of cognitive outcome following anterior temporal lobectomy (Gleissner et al, 2002;Ojemann & Dodrill, 1985;Wolf et al, 1993).…”
Section: Neuropsychological Outcome Following Temporal Lobectomymentioning
confidence: 95%
“…In regard to language, Stafiniak et al (1990) provided a somewhat different view of this idea, proposing that early onset patients have not had time for complete lateralization of language to occur, and thus reorganization is more likely in such individuals and the resultant effects of surgery on language are diminished. Several studies have demonstrated a relationship whereby smaller hippocampal volume (or greater hippocampal sclerosis) was associated with poorer preoperative memory performance, but relatively less postoperative memory decline (e.g., Hermann et al, 1994;Trenerry et al, 1993).…”
Section: Functional Reorganizationmentioning
confidence: 99%